Gender differences in the impact of plasma xanthine oxidoreductase activity on coronary artery spasm. (14th October 2021) - Watanabe, K; Watanabe, T; Otaki, Y; Murase, T; Nakamura, T; Hashimoto, N; Kutsuzawa, D; Kato, S; Tamura, H; Nishiyama, S; Takahashi, H; Arimoto, T; et al.
Abstract: Background: It has been reported that decreased nitric oxide bioavailability due to increased reactive oxygen species (ROS) is one of the most important causes of coronary artery spasm (CAS). Xanthine oxidoreductase (XOR) is the rate-limiting enzyme for uric acid (UA) production and plays a pivotal role in generating ROS. It was reported that the gender differences exist in the impact of serum UA levels on cardiovascular risks. We previously demonstrated that increased plasma XOR activity is significantly associated with the incidence of CAS. However, the gender differences in the impact of plasma XOR activity on CAS remain unclear. Purpose: The aim of this study was to examine the gender differences in the clinical impact of plasma XOR activity on CAS. Methods: We investigated plasma XOR activity in 132 patients suspected for CAS (male, n=78; female, n=54), and underwent intracoronary acetylcholine provocation test. XOR activity assay was performed using stable isotope-labeled substrate and liquid chromatography-triple quadrupole mass spectrometry. Provoked CAS was defined as total or subtotal occlusion (≥90%) with accompanying symptoms of chest pain and/or ischemic ST-segment changes on the electrocardiogram. We excluded the patients who had significant coronary artery stenosis (≥50%) and/or were taking XOR inhibitors. Results: Plasma XOR activity was significantly lower in female compared with male patients (30.3 pmol/h/mL, interquartile range (IQR) 22.8–42.7 vs. 51.7 pmol/h/mL, IQR 34.7–101.8; P<0.001). CAS was provoked in 36 male patients and 17 female patients, and they each had significantly higher plasma XOR activity compared with those without, respectively. Multivariate logistic regression analysis showed that plasma XOR activity was independently associated with the incidence of CAS in both genders after adjustment for confounding factors. The optimal cut-off values for predicting CAS were lower in female than those in male patients (52.3 vs. 91.6 pmol/h/mL). Multivariate analysis demonstrated that female patients with high XOR activity (≥52.3 pmol/h/mL; odds ratio [OR] 22.6, P<0.001) exhibited a higher incidence of CAS compared with that in male patients (≥91.6 pmol/h/mL; OR 8.2, P<0.001). Conclusions: Plasma XOR activity was an independent predictor for the incidence of CAS in both genders. The impact of plasma XOR activity on CAS was stronger in female patients than in male patients. FUNDunding Acknowledgement: Type of funding sources: None.